1985
DOI: 10.1002/etc.5620040113
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure assessment: Experience under the toxic substances control act

Abstract: The Toxic Substances Control Act (TSCA) has focused governmental attention on the process of assessing the hazards from commercial chemicals. Environmental behavior and impact must be projected before the chemical is released. This requires a knowledge of the environment, relevancy of laboratory data, extent of necessary data and interpretation of those data for future impacts. The responsibility for the data rests with the manufacturer. The key criterion involves a determination of “unreasonable risk.” Six ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…An atmospheric half-life with respect to photolysis ranged from 0.5 to 1 d (USEPA 1985; Jori et al 1986). The mand p-xylene isomers are also 80 and 71% biodegradable, respectively, in BOD tests using municipal sewage seed, indicating that xylenes are readily biodegradable (Bridie et al 1979;Daniels et al 1985). However, Bridie et al (1979) found a-xylene to be only 57% biodegradable in BOD tests.…”
Section: N) Xylenesmentioning
confidence: 83%
See 4 more Smart Citations
“…An atmospheric half-life with respect to photolysis ranged from 0.5 to 1 d (USEPA 1985; Jori et al 1986). The mand p-xylene isomers are also 80 and 71% biodegradable, respectively, in BOD tests using municipal sewage seed, indicating that xylenes are readily biodegradable (Bridie et al 1979;Daniels et al 1985). However, Bridie et al (1979) found a-xylene to be only 57% biodegradable in BOD tests.…”
Section: N) Xylenesmentioning
confidence: 83%
“…The predominant fate process is volatilization from water (Klingman et al 1975;Daniels et al 1985). Xylene vapor pressure averages 6 mm Hg at 20°C (Hunter et al 1984;Daniels et al 1985) with H values ranging from 0.017 to 0.022 atm m 3 /mol for o-xylene and p-xylene, respectively (Hunter et al 1984).…”
Section: N) Xylenesmentioning
confidence: 98%
See 3 more Smart Citations